The Traits Of Social Ideal In Russian Philosophy Of the XIX Century - Bystriantsev, Sergei; Bagandova, Elmira; Yeghiazaryan, Syuzanna; Bystriantsev, Peresvet; Pleshkov, Evgeny; Saakyan, Ishkhan (Տիգրան Մեծ)
Russian social philosophers developed ideas and disputed them with the European philosophers and social thinkers of the XIX century. The main characteristics of Russian philosophy were the natural synthesis of religious, philosophical and scientific knowledge about the society. That is why any phenomenon of social life had to be analyzed from the point of view of ideal start, theoretical example, to which the practice of social action should correspond.
Keywords: History of philosophy